2001
DOI: 10.1046/j.1365-2265.2001.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled trial of long‐term oral combined continuous hormone replacement therapy in postmenopausal women: effects on arterial compliance and endothelial function

Abstract: In this long-term, randomized placebo-controlled trial, oral continuous HRT with combined oestradiol and norethisterone in healthy postmenopausal women did not improve a spectrum of indices of arterial function compared to placebo. These results suggest that HRT might not be of cardiovascular benefit in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 46 publications
2
30
0
2
Order By: Relevance
“…Estrogen may reduce arterial stiffness through a benefi cial effect on endothelial function. Although we have reported that HRT infl uences arterial stiffness determined by baPWV [12] , there are some studies with confl icting results [9,10] . We have shown that the defi ciency of endogenous estrogen deteriorates endothelial function by fl ow-mediated dilatation within 1 week [22] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Estrogen may reduce arterial stiffness through a benefi cial effect on endothelial function. Although we have reported that HRT infl uences arterial stiffness determined by baPWV [12] , there are some studies with confl icting results [9,10] . We have shown that the defi ciency of endogenous estrogen deteriorates endothelial function by fl ow-mediated dilatation within 1 week [22] .…”
Section: Discussionmentioning
confidence: 96%
“…In postmenopausal women, it has been shown that HRT improves cfPWV, but not femoral artery to the dorsalis pedis PWV (fdPWV) [9] . On the other hand, randomized placebocontrolled trials showed that HRT did not improve both cfPWV and fdPWV [10,11] . We previously reported that estrogen administration improved baPWV in normotensive postmenopausal women [12] .…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, the findings from our dietary soy/ isoflavone study in normotensive subjects noted a significant reduction in blood pressure. 7 Given these discrepancies and the fact that estrogen does not reduce blood pressure, 36 the hypotensive effects of soy may not be mediated by estrogenic mechanisms and be unrelated to isoflavones.…”
Section: Teede Et Almentioning
confidence: 99%
“…Estriol has been considered to be an antagonist of estradiol. [14][15][16][17] The data so far available concerning estriol action on the endometrium, myometrium, vagina and breast are ambiguous, and they provide contradictory information. [18][19][20][21] It seems that differences in the affinity, specificity and concentrations of ERs in individual tissues are of much greater importance, together with changes in effector tissues that lead to different responses.…”
Section: Introductionmentioning
confidence: 99%